Uji Antagonis Ekstrak Daun Meniran (Phyllanthus Niruri Linn.) Terhadap Jamur Fusarium Sp. - Irfan Jayadi; Khaerul Ihwan; Baiq Naili Dewi Atika; Dwi Kartika Risfianty; Pahmi Husain; Siti Fajriah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2022)
Meniran (Phyllanthus niruri L) is a type of herb from the Euphorbiaceae family that grows wild in damp and rocky places, such as bushes and soil among the grasses, but has medicinal properties. Meniran also has potential as an antibacterial because it contains many bioactive components such as alkaloids, flavonoids, tannins, and saponins. Gram negative bacteria such as Salmonella sp. and gram-positive bacteria such as Propionibacterium acnes. Fusarium oxysporum is one of the soil-borne pathogens that can attack horticultural crops so that it can affect the decline in plant productivity. Fusarium oxysporum is a pathogenic fungus that causes a disease known as fusarium wilt disease. This fungus is found in the soil by forming three kinds of spores, namely microconidium, macroconidium and claimidospore. This study aims to determine the inhibition or antagonist of meniran leaf extract (Phyllanthus niruri L.) against fusarium sp. meniran against fusarium fungus.